2021
DOI: 10.14778/3489496.3489516
|View full text |Cite
|
Sign up to set email alerts
|

Enabling personal consent in databases

Abstract: Users have the right to consent to the use of their data, but current methods are limited to very coarse-grained expressions of consent, as "opt-in/opt-out" choices for certain uses. In this paper we identify the need for fine-grained consent management and formalize how to express and manage user consent and personal contracts of data usage in relational databases. Unlike privacy approaches, our focus is not on preserving confidentiality against an adversary, but rather cooperate with a trusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Konstantinidis et al [23] proposed a database-level consent evaluation method. The authors proposed a method to evaluate consent information and apply it to the attributes in the tables of the database.…”
Section: B Consent-based Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Konstantinidis et al [23] proposed a database-level consent evaluation method. The authors proposed a method to evaluate consent information and apply it to the attributes in the tables of the database.…”
Section: B Consent-based Sharingmentioning
confidence: 99%
“…In the literature, apart from research on privacy-preserving [12]- [16], consent-based approaches have mainly focused on obtaining consent from the data providers and/or managing data access mechanisms according to the obtained consent [17]- [21], and there are only few studies [22], [23] that have tackled consent-based personal data processing and sharing. However, there are many cases [24]- [26] showed that violations of consent occur when companies utilize personal data.…”
mentioning
confidence: 99%